Cases on collaboration in virtual learning environments processes and interactions - Russell, Donna, 1955- (Information Science Reference, 2010)
"As emerging technologies increase the potential for constructivist learning processes and responses, it is critical that educational researchers, instructional designers, cognitive scientists, and information scientists become more aware of advances in these correlating fields"--IGI Global website.